Nutritional status of rubber growing soil in the Moneragala district - Dharmakeerthi R S; Jayasinghe W K; Silva S N; Yakandawala A (Journal of the Rubber Research Institute of Sri Lanka, 2005)
DL
Keywords: Intermediate zone; Moneragala; Nutrients; Rubber growing soils; Urease activity